Photoacoustic Imaging for Tumor Detection: An in vitro Simulation Study - Moosa, Arwa A.; Hussain, Mohammed A.; Moosa, Arwa A. (Iraqi Journal of Laser, 2019)
Photoacoustic is a unique imaging method that combines the absorption contrast of light or radio frequency waves with ultrasound resolution. When the deposition of this energy is sufficiently short, a thermo-elastic expansion takes place whereby acoustic waves are generated. These waves can be recorded and stored to construct an image. This work presents experimental procedure of laser photoacoustic two dimensional imaging to detect tumor embedded within normal tissue. The experimental work is accomplished using phantoms that are sandwiched from fish heart or blood sac (simulating a tumor) 1-14mm mean diameter embedded within chicken breast to simulate a real tissue. Nd: YAG laser of 1.064μm and 532nm wavelengths, 10ns pulse duration, 445mJ pulse energy has been used to induce the acoustic wave signal in these targets. The acoustic signal is then filtered and analyzed to construct the target image. The analysis of experimental data and image construction has been accomplished using matlab software. The measurement analysis showed reasonable agreement between the estimated object dimension and the actual object size. The error in fish heart object dimension ranged from -14% to +9%, and the maximum error in Blood sac object dimension was -55%. The object dimensional error increased to -92% when the laser spot was magnified from 2mm to 45mm (to cover the phantom area) as the energy density decreases significantly.